Guarantees Of The Right To Education Of Citizens In The Constitution Of The Republic Of Uzbekistan: Legal Basis And Mechanisms Of Implementation - Kurambayev, Sardor (International Conference on Global Trends and Innovations in Multidisciplinary Research, 2026)
This article examines the guarantees of citizens’ right to education enshrined in the Constitution of the Republic of Uzbekistan, their legal foundations, and implementation mechanisms based on a literature review and the author’s independent scholarly analysis. The findings indicate that the updated Constitution has significantly expanded the scope of the right to education, and the introduction of new provisions related to inclusive education, academic freedom, and the recognition of teachers’ work has marked a qualitatively new stage in the development of this field.